FOUNDATIONS OF REGIONAL MONETARY INTEGRATION - Al-Hoderi, Mukhamed (Farabi Journal of Social Sciences, 2020)
The statistical data on foreign investments in the EAEU countries, on the share of gross volumes of mutual trade in the total volume of foreign trade in the EAEU as a whole and in the EAEU member states, are given. Analysis of mutual trade and investment indicators showed an insufficient level of economic convergence in the EAEU, assessed from the standpoint of the mutual trade intensity and mutual foreign direct investment intensity. At the moment, the volumes and dynamics of trade and investment flow between the EAEU member states do not cause an objective need for a transition to monetary cooperation at the level of a currency union. This research allows us to consider the problem of transition to monetary integration between the countries participating in the EAEU from the importance standpoint of economic prerequisites. The practical significance of the work lies in the substantiation of the objective prerequisites for the formation and creation of a monetary union in the course of regional integration processes development.